2021
DOI: 10.1177/10732748211047408
|View full text |Cite
|
Sign up to set email alerts
|

Age Under 30 Years As a Predictor of Poor Survival in a Cohort of Mexican Women With Breast Cancer

Abstract: Introduction Young women under 30 years with breast cancer (BC) are an emerging challenge. The purpose is to identify prognostic factors for survival in young women under 30 years of age with BC. Material and methods A retrospective cohort study was conducted among women younger than or equal to 40 years with BC and who were treated at the State Cancer Center during the period 2012–2017. Overall survival was assessed using the Kaplan–Meier method and the log-rank test. Univariate and multivariate analysis asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Women aged <40 years were 44% (HR = 1.44; 95% CI: 1.27–1.64) and 9% (HR = 1.09; 95% CI: 1.03–1.15) more likely to die of stage I and stage II breast cancer, respectively [ 204 ]. Further, a significantly lower overall survival (OS) and disease-free survival (DFS) have been reported in Mexican, Hungarian, and Indian cohorts in very young (<35 years of age) women compared to young (<45 years), which may be related to the more aggressive subtypes of tumours developing in earlier ages [ 205 , 206 , 207 ]. Bajpai et al conducted a prospective cohort study enrolling 1228 women aged ≤40 years.…”
Section: Prognosismentioning
confidence: 99%
“…Women aged <40 years were 44% (HR = 1.44; 95% CI: 1.27–1.64) and 9% (HR = 1.09; 95% CI: 1.03–1.15) more likely to die of stage I and stage II breast cancer, respectively [ 204 ]. Further, a significantly lower overall survival (OS) and disease-free survival (DFS) have been reported in Mexican, Hungarian, and Indian cohorts in very young (<35 years of age) women compared to young (<45 years), which may be related to the more aggressive subtypes of tumours developing in earlier ages [ 205 , 206 , 207 ]. Bajpai et al conducted a prospective cohort study enrolling 1228 women aged ≤40 years.…”
Section: Prognosismentioning
confidence: 99%
“…Studies have shown that BCYW is generally more aggressive with a poorer prognosis than BC in older patients [ 16 , 17 , 18 ]. A high prevalence of TNBC, basal-like tumors, and luminal B exists in BCYW [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, the effect of cancer subtypes on the genome of women with BC aged ≤40 years remains poorly studied.…”
Section: Resultsmentioning
confidence: 99%
“…The range of clinical characteristics exhibited in BCYW is distinct from that exhibited in older premenopausal and postmenopausal women with BC; thus, BCYW could be considered a subset of premenopausal diseases. BCYW exhibits more aggressive cancer subtypes (such as TNBC/basal, HER2-positive, and luminal B) than BC in older patients [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The prognosis of BCYW is generally worse than that of BC in older patients, presumably due to its aggressive subtypes, detection at an advanced stage, and a high recurrence rate [ 1 , 6 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of these molecular subtypes varies across age groups, with luminal B, HER2-positive, and basal-like tumors being more prevalent in younger women compared to older breast cancer patients [ 1 , 2 , 18 ]. In the BCYW age group, a significant percentage (about 34%–37 %) of women have triple-negative breast cancers in different studies [ [19] , [20] , [21] ], which may look like homogeneous hypoechoic lesions with smooth rounded borders; these can often be misreported as fibroadenomas and ignored. 3) some patients are young mothers who may be mislabeled as having galactoceles.…”
Section: Contributing Factors – Examplesmentioning
confidence: 99%